Визначення параметрів струминного та пульсаційного гомогенізаторів молока при їх промисловому застосуванні - Кюрчев, Сергій Володимирович; Самойчук, Кирило Олегович; Ломейко, Олександр Петрович; Kiurchev, Serhii; Samoichuk, Kyryl; Lomeiko, Oleksandr (Запоріжжя : 2024, 2024)
UA: Для впровадження розроблених енергоефективних струминного та пульсаційного гомогенізаторів необхідна розробка технології їх використання на виробництві. А для цього – основною перешкодою є відсутність даних з співставлення режимів клапанної (існуючої) гомогенізації з знов розробленими гомогенізаторами. Для розробки технології переробки молока при використанні цих двох гомогенізаторів, необхідно встановити залежність між режимами клапанної гомогенізації з основними параметрами нових гомогенізаторів. Отримані в результаті досліджень дані дають змогу визначити необхідні основні технологічні параметри, які визначають якість гомогенізації, для розроблених гомогенізаторів (пульсаційного та струминного) в залежності від даних, вказаних для клапанної гомогенізації. Таким чином будь-яка класична технологічна схема виробництва молочних продуктів може бути легко застосована для використання розроблених гомогенізаторів зі зниженими енерговитратами. EN: One of the main problems of the food and processing industry of Ukraine is the insufficient technical and technological efficiency of the production of products, which are finely dispersed emulsions. For the implementation of the developed effective jet and pulsation homogenizers, it is necessary to develop the technology of their use in production. And for this, the main obstacle is the lack of data on the comparison of valve (existing) homogenization modes with newly developed homogenizers. For a jet homogenizer, the main parameter that determines the degree of dispersion and energy consumption of the process is the flow rate of skimmed milk. And for pulsating - the frequency and amplitude of piston oscillation. To develop a milk processing technology when using these two homogenizers, it is necessary to establish the relationship between valve homogenization modes (which are prescribed in the existing technological schemes for the production of dairy products) with the main parameters of the new homogenizers. The purpose of this article is to determine the parameters of jet and pulsating milk homogenizers when they are used industrially instead of valve homogenizers. To achieve the set goal: the correspondence between the pressure of the valve homogenization and the speed of supply of skimmed milk in the jet homogenizer is determined; the correspondence between valve homogenization pressure and the frequency and amplitude of piston oscillation in the pulsating homogenizer is determined; the correspondence between the specific energy consumption of valve homogenization and jet and pulsation homogenization is determined. The data obtained as a result of research make it possible to determine the necessary basic technological parameters that determine the quality of homogenization for the developed homogenizers (pulsation and jet), depending on the data specified for valve homogenization. Thus, any classic technological scheme of dairy production can be easily applied to use the developed homogenizers with reduced energy consumption.
Determination of the parameters of flow and pulsation milk homogenizers in their industrial application
Keywords: гомогенізація; диспергування молока; струминний гомогенізатор; пульсаційний гомогенізатора; технологія; homogenization; milk dispersion; jet homogenizer; pulsating homogenizer; technology